2020
DOI: 10.1177/1534735420969818
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Physical Activity in Patients With Breast Cancer: During and/or After Chemotherapy? Impact on Cardiorespiratory Fitness. A 3-Arm Randomized Controlled Trial (APAC)

Abstract: Objectives: Physical activity (PA) programs are recommended for breast cancer care. However, their modalities remain to be discussed. This study determined the best time to begin a personalized or adapted program based on cardiopulmonary exercise test function. This randomized controlled trial evaluated the effect of home-based adapted PA (APA) performed during or after treatment on cardiorespiratory fitness (CRF) at 12 months. Method: The primary endpoint was the peak oxygen consumption (VO2peak) at 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Our group is assessing a tailored exercise program for breast cancer patients undergoing various treatments (S, SR, SE, SC). Other studies have evaluated physical activity regimens during chemotherapy and found improvements in cardiorespiratory fitness [26] chemotherapy related fatigue [27] and less nausea and pain [28]. Our data suggest the initial 3 months post initial surgical intervention to be the most dynamic and potentially important period for addressing weight loss changes in patients with early stage breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 59%
“…Our group is assessing a tailored exercise program for breast cancer patients undergoing various treatments (S, SR, SE, SC). Other studies have evaluated physical activity regimens during chemotherapy and found improvements in cardiorespiratory fitness [26] chemotherapy related fatigue [27] and less nausea and pain [28]. Our data suggest the initial 3 months post initial surgical intervention to be the most dynamic and potentially important period for addressing weight loss changes in patients with early stage breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 59%
“…Our group is assessing a tailored exercise program for breast cancer patients undergoing various treatments (S, SR, SE, SC). Other studies have evaluated physical activity regimens during chemotherapy and found improvements in cardiorespiratory tness (26) chemotherapy related fatigue (27) and less nausea and pain (28). Our data suggest the initial 3 months post initial surgical intervention to be the most dynamic and potentially important period for addressing weight loss changes in patients with early stage breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 57%
“…Data were collected from the patients included in our two prospective trials, the SAPA ( —NCT01322412) [ 11 ] and APAC ( —NCT0179561) trials [ 23 ], both of which were conducted at Limoges University Hospital. Eligible patients were women aged 18–75 years with early-stage breast cancer treated with chemotherapy (neoadjuvant or adjuvant) followed by radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…The first VT was defined as being when CO 2 production began to increase disproportionately to O 2 consumption, as measured using the Wasserman method [ 26 ]. This test was supervised by a respiratory physiologist (more details in previous work) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation